Graphic standards field guide to home inspections - Gladstone, Stephen, 1949- (Hoboken, N.J. : John Wiley & Sons, 2011)
'Part of the Wiley's Graphic Standard Field Guides series, Graphic Standards Field Guide to Home Inspection provides standards, guidelines, and terminology for professional home inspectors. Designed for portability and quick-reference, this unique book discusses standards of practice for home inspection, the most common defects and potential remedies, standard and high-tech tools of the trade, and more. The website includes downloadable illustrations for inspection reports. Putting all the key information at the reader's fingertips out in the field, this is an essential tool for home inspectors, architects, engineers, and contractors'--
'Graphic Standards Field Guide to Home Inspection is the reference for home inspectors, architects, engineers, and contractors who need to evaluate an existing residential property. This field guide provides a qucik reference to the standards, guidelines, and terminology that a professional inspecting a home needs, in an easily accessible and highly visual format-- the trademark of a Graphic Standards title. This book pairs standard architectural details and drawings that professionals count on from Graphic Standards with photographs and interpretive information that are essential when outside the office. The small trim size and durable binding makes it easy for anyone inspecting a home to keep this resource on hand'--
Includes index.
Keywords: Dwellings -- Inspection -- Handbooks, manuals, etc